2004
DOI: 10.18388/abp.2004_3556
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane-mediated induction of a phase 2 detoxifying enzyme NAD(P)H:quinone reductase and apoptosis in human lymphoblastoid cells.

Abstract: The effect of sulforaphane on human lymphoblastoid cells originating from a patient of a high cancer risk was studied. Sulforaphane (SFN) is a naturally occurring substance of chemopreventive activity. In our study, changes in cell growth, induction of apoptosis and phase 2 enzymes as well as glutathione level were examined. Apoptosis was tested by confocal microscopy at three stages: change in mitochondrial membrane potential, caspase activation and phosphatidylserine externalization. We show that SFN increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…In our cytotoxicity results, the values of CC 50 for these paired cells are 12/33 µM and 15/11 µM, respectively (Figure ). In other reports, it was suggested that the IC 50 values of SFN were 1–10 µM in colon cancer cell lines , 18 and 20 µM in human leukemia cells , 3.9 µM in human lymphoblastoid cells and 8.1–9.5 µM in human breast cancer cells . Therefore, SFN showed similar cytotoxicity in NPC cells to other types of cancer cells.…”
Section: Discussionmentioning
confidence: 76%
“…In our cytotoxicity results, the values of CC 50 for these paired cells are 12/33 µM and 15/11 µM, respectively (Figure ). In other reports, it was suggested that the IC 50 values of SFN were 1–10 µM in colon cancer cell lines , 18 and 20 µM in human leukemia cells , 3.9 µM in human lymphoblastoid cells and 8.1–9.5 µM in human breast cancer cells . Therefore, SFN showed similar cytotoxicity in NPC cells to other types of cancer cells.…”
Section: Discussionmentioning
confidence: 76%
“…SFN has been well known as a potent inducer of the phase II antioxidant enzymes including HO‐1 [2,3]. Treatment of mouse cortical cells with SFN resulted in a significant induction of HO‐1 together with an increase in ARE reporter activity (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 97%
“…A representative compound of new generation PP(Ala) 2 (Arg) 2 -dialanine derivative of protoporphyrin IX was investigated as a potentially more effective drug in comparison to the PPIX to PDT (Graczyk & Konarski, 1995, Graczyk & Konarski, 1997Graczyk, 1999). The cell viability under influence of PDT depending on time after irradiation (controls: non-toxic energy doses and photosensitizer concentrations) and then cell death mechanism by transmembrane mitochondrial potential -early stage of apoptosis were studied (Misiewicz et al, 2003;Misiewicz et al, 2004;Misiewicz-Krzemińska et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In healthy cells (polarized mitochondria) the dye accumulates and forms J-aggregates giving red fluorescence. In apoptotic cells (depolarized mitochondria) monomeric dye gives green fluorescence (the dye stays in the cytoplasm) (Misiewicz et al, 2003;Misiewicz et al, 2004;Misiewicz-Krzemińska et al, 2009;Reers et al, 1991;Smiley et al, 1991).…”
Section: Chemicalsmentioning
confidence: 99%